Verifying learning success: assessment and certification of student ultrasound education - Ricarda Neubauer; Florian Recker; Johannes Weimer; Christian Jenssen; Dieter Nürnberg; Thomas Karlas; Susan Campbell Westerway; Johannes P. Ruppert; Nils Daum; Anna Gschmack; Yi Dong; Kathleen Möller; et al. (BMC Medical Education)
Abstract Student ultrasound education (SUSE) is currently composed of heterogeneous curricular training formats, and new approaches are continually being explored to enhance undergraduate ultrasound training. Based on a literature review, this report aims to analyze and compare different forms and methods of assessment of acquired skills in ultrasound training. Therefore, the advantages and disadvantages of assessment formats and certification systems used in SUSE were discussed collaboratively between medical students, postgraduate physicians, and medical didactics experts. Ultrasound competency should be tested using structured examination formats that are objective and standardized. In addition to cognitive skills, the examination format should cover translational and behavioral components. Self-assessments and evaluations provide additional valuable perspectives. Certification systems can contribute to quality assurance by externally ensuring the achievement of milestones in SUSE. They also have the potential to support the necessary standardization of undergraduate ultrasound teaching by aligning the curricular learning objectives with qualifications to be achieved.